2016
DOI: 10.1002/adfm.201602963
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Prodrug Nanoparticles for Acid‐Triggered Precise Imaging and Organelle‐Specific Combination Cancer Therapy

Abstract: Integration of chemotherapy with photodynamic therapy (PDT) has been emerging as a novel strategy for treatment of triple negative breast cancer (TNBC). However, the clinical translation of this approach is hindered by the unwanted dark toxicity due to the “always‐on” model and low tumor specificity of currently approved photosensitizer (PS). Here, the design of a multifunctional prodrug nanoparticle (NP) is described for precise imaging and organelle‐specific combination cancer therapy. The prodrug NP is comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 52 publications
0
54
0
Order By: Relevance
“…19 With the aim to overcome the PS toxicity caused by non-specic targeting, B. Feng et al synthesized a multifunctional prodrug nanosystem loaded with hexadecyl-oxaliplatin-trimethyleneamine (prodrug, HOT) and derivative of Chlorin e6 (acid-activatable PS, AC). 20 Aer the nanosystem was modied with iRGD, a targeting ligand, it could function for tumor homing and penetration. AC will minimize the toxicity during the blood circulation, while its specic acid-response in orthotopic or metastatic tumor could enhance the uorescence imaging and PDT.…”
Section: Ros and Photodynamic Therapymentioning
confidence: 99%
“…19 With the aim to overcome the PS toxicity caused by non-specic targeting, B. Feng et al synthesized a multifunctional prodrug nanosystem loaded with hexadecyl-oxaliplatin-trimethyleneamine (prodrug, HOT) and derivative of Chlorin e6 (acid-activatable PS, AC). 20 Aer the nanosystem was modied with iRGD, a targeting ligand, it could function for tumor homing and penetration. AC will minimize the toxicity during the blood circulation, while its specic acid-response in orthotopic or metastatic tumor could enhance the uorescence imaging and PDT.…”
Section: Ros and Photodynamic Therapymentioning
confidence: 99%
“…Meanwhile, several independent groups including ourselves have demonstrated that NIR laser‐conducted photodynamic therapy (PDT) prompted up the drug release in the tumor tissue or inside the cancer cells by inducing reactive oxygen species (ROS) generation to degrade the ECM or endocytic vesicles . Moreover, PDT was utilized to activate the therapeutic payloads and selectively destroy the tumor cells without affecting the nearby normal tissues . Despite being promising, the design of versatile nanovectors to address the sequential barriers for highly efficient cancer therapy remains a formidable challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Oxaliplatin (OXA) and DOX are both the first‐line chemotherapeutics clinically used for the treatment of various carcinomas including colonic and breast cancers . To demonstrate the potential of ELTSL for combination chemotherapy of TNBC, we first synthesized a lipophilic OXA prodrug of hexadecyl‐oxaliplatin carboxylic acid (HOC) according to a procedure we reported previously (Figures S10 and S11, Supporting Information) . HOC is a Pt (IV) prodrug, which is inert in the blood circulation and is activated in the tumor cells by reducing HOC (IV) to OXA (II) with the endogenous glutathione (GSH).…”
Section: Resultsmentioning
confidence: 99%